ANALISA PEMILIHAN MODA DAN WAKTU EVAKUASI BENCANA TSUNAMI DI KECAMATAN KUTA RAJA BANDA ACEH - Taufik Taufik; Sugiarto Sugiarto; Muhammad Isya (Prodi Magister Teknik Sipil Unsyiah, 2018)
Banda Aceh City, the capital of Aceh province, is particularly vulnerable to the tsunami. One of the most vulnerable sub-district in Banda Aceh is the Kuta Raja sub-district, which has a high tsunami threat level. Realizing the harmful effects that could be caused by the earthquake disaster. Therefore, disaster mitigation needs to be considered in order to reduce casualties and to minimize the risk of disaster that will occur in the future. One of the most important things in the evacuation planning is that mode and time of evacuation choices by the residents. Residents may be considered the safest mode and the correct time to evacuate. In this case, fastest mode and nearest escape building would be influenced factor for residents in selecting mode and time to evacuate. Therefore, in this study, we consider two mode choices, that is motorized and non-motorized transports. This study aims at analyzing the mode and time to evacuate choice made by the residents. The stated preference of questionnaire survey method is used to obtained necessary data set from the respondents. The discrete choice model namely binomial logit model is then governed to explore the behavioral response by respondents in selecting mode and time to evacuate. The result from the analysis reveals that the average time to evacuate less than 30 minutes was selected for the respondent who considers evacuating to the evacuation building within the radius of 15 km from their home. The probability to select a time to evacuate less than 30 minutes and evacuate distance within the radius of 15 km is about 71%. The remaining probability is around 29% to select a time to evacuate more than 30 minutes with evacuate distance more than the radius of 15 km. As for mode choice model depicts that the motorized transport is shown dominated up to 89% while for the non-motorized accounting up to 11%. The households characteristics that influencing the mode and time to evacuate selection are income, employment status, age and number of the child within a household.